Incidence of Gingival Mucosa Karyolysis in the Use of Food Coloring as A Dental Plaque Detection Material (Study on Mus Musculus)” - Handayatun, Naning Nur; Rudi, David; Fitria, Karin Tika; Fairuz, Fairuz (Indonesian Journal of Global Health Research, 2024)
Bacteria in dental and oral diseases can lead to systemic issues like kidney and heart disease, emphasizing the importance of maintaining oral hygiene. Disclosing solution, a plaque-revealing agent, is pivotal in assessing plaque removal efficacy. The optimal concentration of rose pink food coloring for plaque visibility is 2.5 g/20 ml water. However, the potential impact of this coloring on oral epithelium remains unstudied. Objective: This research aimed to evaluate the effect of disclosing solution food coloring on the gingival mucosal layer in mice. Pure experimental research with a control group design involved 6 mice (Mus musculus) each in treatment and control groups. Erythrocyn, derived from rose pink food coloring, was applied to mice’s gingiva for 2 minutes daily over 7 days. Labio-gingival epithelial cells were then sampled and analyzed using the modified Feulgen-Roseenbeck method. 58.33% of mice showed karyolysis in gingival epithelial cells, contrasting with no karyolysis in lip mucosa. Careful management of food coloring-containing erythrosine as a plaque detection agent is crucial to prevent contact with oral mucosa or prompt cleaning if contact occurs.